2018
DOI: 10.1016/j.yexcr.2017.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Functional role for stable microtubules in lens fiber cell elongation

Abstract: The process of tissue morphogenesis, especially for tissues reliant on the establishment of a specific cytoarchitecture for their functionality, depends a balanced interplay between cytoskeletal elements and their interactions with cell adhesion molecules. The microtubule cytoskeleton, which has many roles in the cell, is a determinant of directional cell migration, a process that underlies many aspects of development. We investigated the role of microtubules in development of the lens, a tissue where cell elo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 101 publications
0
20
0
Order By: Relevance
“…The C-terminal ends of intact AQP0 at the outer cortex interact with other proteins, such as beaded filament proteins filensin and CP49, to provide anchorage, fiber cell architecture, and lens biomechanics. Interaction of adhesion protein N-Cadherin and cytoskeletal elements during fiber cell elongation has been reported 69. CTCA is necessary to maintain the proper RING, which is low at the outer cortex and high in the central nucleus where it is more or less constant 70,71.…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal ends of intact AQP0 at the outer cortex interact with other proteins, such as beaded filament proteins filensin and CP49, to provide anchorage, fiber cell architecture, and lens biomechanics. Interaction of adhesion protein N-Cadherin and cytoskeletal elements during fiber cell elongation has been reported 69. CTCA is necessary to maintain the proper RING, which is low at the outer cortex and high in the central nucleus where it is more or less constant 70,71.…”
Section: Discussionmentioning
confidence: 99%
“…Microtubules function during cell division ( Memberg and Hall, 1995 ), migration ( Francis et al, 2011 ), and structural maintenance and changes ( Logan et al, 2018 ) among other cellular processes, and therefore, the expression of TUBB3 in NP cells during neurulation suggests that the beta-III isoform of the protein functions in one of these aspects at this stage. Since the NP is undergoing drastic morphological changes during neural tube closure, and the cells are also proliferating, the specific role of TUBB3 is difficult to pinpoint.…”
Section: Resultsmentioning
confidence: 99%
“…45,47,[59][60][61][62][63] Microtubules' role in cell functioning greatly depends on its ability to coordinate the functioning of other cellular elements, including other cytoskeletal components. [64][65][66][67][68] This has proven especially true in the field of cellular migration, with microtubules shown to have both direct and indirect effects on the actomyosin machinery in motile cells, partly through regulation of their stability. [64][65][66][67][68] Newer research has also demonstrated that microtubule interaction with cellular elements includes not only cytoskeletal elements and cytoplasmic organelles, but also cell-cell junctional proteins.…”
Section: Introductionmentioning
confidence: 99%
“…[64][65][66][67][68] This has proven especially true in the field of cellular migration, with microtubules shown to have both direct and indirect effects on the actomyosin machinery in motile cells, partly through regulation of their stability. [64][65][66][67][68] Newer research has also demonstrated that microtubule interaction with cellular elements includes not only cytoskeletal elements and cytoplasmic organelles, but also cell-cell junctional proteins. [68][69][70][71][72] Here, we look at the expanding role of microtubules in cellular functions and how microtubules may serve as a keystone of cytoskeletal coordination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation